Breaking the silence: Addressing sexual health challenges among migrant and refugee women - Zohra S Lassi; Negin Mirzaei Damabi; Mumtaz Begum; Jodie C Avery; Salima Meherali (Women's Health)
This editorial addresses the critical yet often overlooked issue of sexual health among migrant and refugee women. With nearly half of the world’s 281 million international migrants being women, their unique health challenges demand urgent attention. As a conceptual discussion, this editorial does not present empirical data but rather synthesizes existing literature and expert insights to explore the multifaceted barriers these women face, including financial constraints, language obstacles, cultural taboos, and social exclusion. We examine the complex interplay between acculturation and sexual function, emphasizing how cultural transitions influence sexual well-being. The discussion explores how cultural background shapes sexual attitudes, highlighting the need for culturally sensitive approaches in healthcare delivery. We propose multifaceted solutions, including developing culturally competent healthcare services, implementing targeted education programs, and improving research methodologies. This editorial aims to break the silence surrounding these issues and calls for concerted efforts to address the sexual health needs of migrant and refugee women, ultimately fostering healthier, more equitable societies.